Técnicas de evaluación constructivista para la mejora del rendimiento académico de los estudiantes, en Ciencias Naturales. Año lectivo 2022-2023. - Mejía Rogel, Juleysi Anabel (2023)
In the teaching and learning process, constructivist assessment techniques adapted to class content allow optimizing the process and improving the academic performance of students. In that way, for the development of this research work, the objective was: <<Improve the academic performance of students through the implementation of constructivist evaluation techniques, which allows optimizing the teaching and learning process in the subject of Natural Sciences of the eighth year of Basic General Education of the Educative Unit "Adolfo Valarezo", academic year 2022-2023>>. In the investigation, the inductive method was used, starting from the identified problem and through the bibliographic search, an intervention proposal was elaborated and developed to influence such problem. Has a qualitative approach, because important characteristics related to the detected problem were determined. On the other hand, it is of the Participatory Action Research type. Because, the problem was intervened through the implementation of the intervention proposal that actively involved the students and the researcher, achieving the improvement of the academic performance of the students. It is transversal, since it was developed during a relatively short period of time, from the diagnosis to the discussion of results. The information obtained allowed us to establish that the evaluation techniques implemented, such as: model development, solving word search, observation, puzzle construction, among others; were the most accepted by the students and generated improvements in their academic performance. Based on this, it is concluded that all the constructivist evaluation techniques applied, strengthen the development of variables associated with academic performance, among them: study skills, organization, concentration in the study and the ability to relate new knowledge with existing ones, being effective regarding the improvement of the academic performance of the students. Key words: Learning assessment, constructivism, teaching-learning process, constructivist assessment, assessment instruments